Delayed addition of nitrogen-rich substrates during composting of municipal waste: Effects on nitrogen loss, greenhouse gas emissions and compost stability. (January 2017) - Nigussie, Abebe; Bruun, Sander; Kuyper, Thomas W.; de Neergaard, Andreas
Abstract: Municipal waste is usually composted with an N-rich substrate, such as manure, to increase the N content of the product. This means that a significant amount of nitrogen can be lost during composting. The objectives of this study were (i) to investigate the effect of split addition of a nitrogen-rich substrate (poultry manure) on nitrogen losses and greenhouse gas emissions during composting and to link this effect to different bulking agents (coffee husks and sawdust), and (ii) to assess the effect of split addition of a nitrogen-rich substrate on compost stability and sanitisation. The results showed that split addition of the nitrogen-rich substrate reduced nitrogen losses by 9% when sawdust was used and 20% when coffee husks were used as the bulking agent. Depending on the bulking agent used, split addition increased cumulative N2 O emissions by 400–600% compared to single addition. In contrast, single addition increased methane emissions by up to 50% compared to split addition of the substrate. Hence, the timing of the addition of the N-rich substrate had only a marginal effect on total non-CO2 greenhouse gas emissions. Split addition of the N-rich substrate resulted in compost that was just as stable and effective at completely eradicating weed seeds as single addition. These findings therefore show that split addition of a nitrogen-rich substrate could be an option for increasing the fertilising value of municipal waste compost without having a significant effect on total greenhouse gas emissions or compost stability. Highlights: Nitrogen rich (N-rich) substrate was added at different times during composting. Delayed addition of an N-rich substrate reduced nitrogen loss from compost. The timing of the addition of an N-rich substrate affected N2 O and CH4 emissions. Delayed addition of N-rich substrate resulted in stable compost as early addition.